THE SIGNIFICANCE OF B. AHMEDOV’S SCHOLARLY RESEARCH IN THE STUDY OF THE HISTORY OF AMIR TEMUR AND THE TIMURID PERIOD - Rakhmonberdiev Feruz Makhmudjon ugli (Sciental Journals Publishing, 2025)
This article analyzes B. Ahmedov’s studies devoted to the history of Amir Temur and the Timurid period from historiographical and source-critical perspectives. The aim of the research is to present, in a systematic manner, the scholar’s contribution to Timurid studies during the Soviet era (1960–1991) and the years of independence. In addition, the article examines both the strengths of Ahmedov’s role in re-reading the Timurid legacy beyond ideological frameworks and restoring it to scholarly circulation, as well as several of his debatable interpretations in the field.
Keywords: B. Ahmedov, Timurid studies, Amir Temur, Timurids, Mirzo Ulugh Beg, historiography, source criticism, “Tarikh-i Arba ‘Ulus”, “Tuzukoti Temuriy”.